Penguatan Ketahanan Pangan Keluarga pada Tiga Kampung Lokal di Kabupaten Merauke - Puji Susanty Artiningsih; Beatrix Anna Maria Rahawarin; Jean Laurina Masatuneko; Aguslavia Somalolo Masrianto Palma (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The communities in Senayu, Sanegi, and Boepe Villages have long relied on foraging activities such as hunting and fishing as well as gardening around sago plants to meet their food needs. Reduced access to forests on investor-managed land has increasingly limited these food sources, creating the need for a rapid strategy to optimize home gardens to meet household consumption needs. This Community Service Program (PKM) aims to improve community knowledge and skills in cultivating organic plants, thereby strengthening household food security while supporting sustainable environmental management. The program was carried out through training and mentoring, using a participatory approach that actively involved community members at each stage of the activities. The initiative was conducted by lecturers from Yasanto Agricultural Polytechnic and participated in by 26 residents from Senayu, Sanegi, and Boepe Villages. The process included initial coordination, preparation of tools and materials, six days of organic farming training, and three months of home-garden cultivation mentoring. Evaluation was carried out through field observations, interviews, and documentation. The results show that participants understood and applied organic cultivation techniques, including the production of organic fertilizer and the management of growing media. These practices resulted in vegetable harvests that were used for household consumption, shared with neighbors, and partially sold. The program proved effective in enhancing community capacity and strengthening household food security. The implications include reinforcing sustainable agriculture practices based on local resources, reducing the use of chemical inputs, and providing an empowerment model that can be replicated and adapted in other villages.